Фазообразование в тонкопленочной системе Ni/GaAs - Дукаров, С.В.; Гребенник, И.П. (My University, 1999)
Приводятся результаты исследования взаимодействия в пленках Ni/GaAs в зависимости от температуры и концентрации компонентов. Обсуждаются причины образования фазы переменного состава g-Ni3Ga2 для широкого интервала составов и особенности процесса упорядочения g-фазы в тонких слоях в условиях ориентирующего действия подложки. The results of studying interactions in Ni/GaAs films at various temperatures and concentration of components are given. The reason for the appearance of a phase with variable composition g-Ni3Ga2 within a wide range of concentrations are discussed.
Phase formation in Ni/GaAs thin film system
Keywords: Thin films; gallium arsenide; crystal structure; Research Subject Categories::NATURAL SCIENCES::Physics::Condensed matter physics::Surfaces and interfaces